TI_GERICHTE 11.2010.84 vom 14. Januar 2013 , Lesione della personalità: risarcimento dei danni e riparazione del torto morale - TI Tribunale d'appello (2013)
Lesione della personalità: risarcimento dei danni e riparazione del torto morale